REGENERATION AND ABNORMALITY IN BENTHIC FORAMINIFER ROSALINA LEEI: IMPLICATIONS IN RECONSTRUCTING PAST SALINITY CHANGES (Rivista italiana di Paleontologia e Stratigrafia, 2011)
A laboratory culture experiment has been conducted to assess the response of marginal marine benthic foraminifer Rosalina leei to salinity and associated pH changes. Live specimens of Rosalina leei were subjected to a range (10-35 psu) of salinity. It was observed that hyposaline condition leads to dissolution of the calcareous tests. However, if the hyposaline condition persists only for a short period, then even after considerable dissolution, specimens were able to regenerate the dissolved part of the test. Additionally, in all the specimens subjected to lower than normal salinity, the regenerated chambers were abnormal. The abnormalities included smaller or larger chambers and addition of new chambers in planes different than the normal plane of the tests. The regenerated specimens, however, attained a final size almost equal to that of control specimens that were not subjected to hyposaline conditions. The differential response of R. leei was attributed to decreased seawater pH under hyposaline condition. The findings can help understand the increased abundance of abnormal specimens under ecologically stressed environments.